Effect of Growth Selection on Adipogenic Gene Expression During the Development of the Turkey Breast Muscle - Velleman , Sandra G. (International Journal of Poultry Science, 2014)
The effect of growth selection in turkeys was studied for its effect on the expression of adipogenic genes in the pectoralis major (p. major) muscle both in vivo and in vitro in a random bred control line (RBC2) and a subline F selected long-term from the RBC2 for only increased 16-wk body weight. The expression of the adipogenic transcription factors peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT/enhancer binding protein α (C/EBPα) and stearoyl-CoA desaturase (SCD) were measured in p. major muscle tissue isolated from 18 and 24 d old embryos and 1 and 16-wk old RBC2 and F line turkeys and in vitro with adult myoblasts (satellite cells) isolated from RBC2 and F line turkey p. major muscle tissue during proliferation and differentiation. Both in vivo and in vitro, the F line expressed significantly higher levels of PPARγ, C/EBPα and SCD. The data from the current study provides novel information about the effect of growth selection in turkeys on the potential of fat formation in vivo in the p. major muscle and the possible transdifferentiation of myogenic satellite cells to an adipogenic lineage.